Position Control of Motor Drive Systems: A Data Driven Approach - Hossein Parastvand; Mohammad Javad Khosrowjerdi; Nacer Kouider M'Sirdi (Renewable Energy and Sustainable Development, 2015)
This paper presents a new model free approach to the design of robust PID controller for the position control of electrical machines, such as induction motor, synchronous motor and DC motor faced to un-modeled dynamics. It is illustrated that knowing the frequency response data is sufficient to calculate the family of robust PID controllers that satisfy -norm on the complementary sensitivity function. The usefulness of the proposed approach is demonstrated through simulation on an induction motor drive system.